Do All Children with Epilepsy have Behavioural Problems? A Multivariate Risk Factor Analysis - Shashank Nayak; Puneet Mathur; Ashok Kumar Jain; Himanshu Agrawal; Rahul Bhargava; Amit Gupta; Niti Tripathi (Online Journal of Health & Allied Sciences)
Objective: To identify independent risk factors and their odds ratio for behavioural problems in children with epilepsy. Methodology: This cross-sectional study involved children with epilepsy and matched controls. Epileptic children over 6 years old were selected through non-probability sampling. Children of the same age and gender who visited the pediatric outpatient department for minor ailments served as controls. Behavior was assessed using the Child Behaviour Checklist (CBCL). Pearson’s correlation examined the relationship between behavioral problems, seizure onset age, frequency, and drug therapy duration. Multiple logistic regression after adjustment for confounders like age, gender, maternal education, and socioeconomic status was done. The independent risk factors for behavioral issues in epileptic children were identified and odds ratios calculated. Results: Among 100 children with epilepsy and 100 controls, 44% of epileptic children had behavioral problems versus 20% of controls (P=0.001). Behavioral scores were significantly higher in epileptic patients across all CBCL domains (P<0.001). Only the anxious/depressed domain showed differences between children receiving anti-epileptic monotherapy versus polytherapy (P=0.025). Longer seizure duration (OR=2.4), longer antiepileptic therapy duration (OR=1.8), and higher seizure frequency (OR=2.1) independently predicted behavioral problems in children with epilepsy. Type of seizures (generalized tonic-clonic versus partial) did not predict behaviour problems (OR=0.8). Conclusion: Behavioral problems are not universal among children with epilepsy. Increased seizure frequency and duration are independent risk factors for these issues.